Antibacterial Lyocell fiber and preparation method thereof
Antibacterial Lyocell fibers are prepared by mixing antibacterial ingredients with NMMO alcohol solution at room temperature and adding them to cellulose solution, which solves the problem of limited application of existing blended antibacterial finishing methods, and achieves stable and lasting antibacterial effects and fiber quality protection.
Patent Information
- Application Number
- CN202411676540.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
AI Technical Summary
The existing blended antibacterial finishing methods are limited in application, especially because nanosilver is too expensive and the introduction of copper may lead to system degradation and safety risks.
By mixing the antibacterial ingredients with the NMMO alcohol solution at room temperature to form an antibacterial dispersion and adding it to the cellulose solution, antibacterial Lyocell fibers are prepared by blending to avoid the degradation of copper at high temperatures.
The stable preparation of copper-based antibacterial Lyocell fibers is achieved. The fibers still maintain good antibacterial effects after multiple washes, and the dispersion uniformity of antibacterial components is improved, reducing the risk of blockage during spinning.
Smart Images

Figure CN119571483A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material-modified functional fiber preparation, and more specifically, relates to an antibacterial Lyocell fiber and a preparation method thereof. Background Art
[0002] Lyocell fiber refers to regenerated cellulose fiber prepared by dry-jet wet spinning using an aqueous solution of N-methylmorpholine-N-oxide (NMMO), a direct solvent for cellulose. Compared with traditional viscose fiber and cuprammonium fiber, the production process of Lyocell fiber does not involve cellulose derivatization, theoretically no chemical reaction occurs, and no toxic or harmful gases are produced. It is known as the new generation of green fiber in the 21st century. Lyocell fiber has a smooth surface and good water absorption. The fabric woven from it has both the comfort of natural fiber and the strength of synthetic fiber, and has a texture similar to silk, which is very popular in the high-end fabric market.
[0003] For Lyocell fiber, due to its superior product performance and environmentally friendly process, the market potential is very huge. Therefore, it is an inevitable trend to develop an environmentally friendly antibacterial finishing method to give Lyocell fabric antibacterial properties. At present, the common antibacterial treatment methods for cellulose fibers mainly include coating, impregnation, and stock solution blending. Patents CN214193550U and CN210916769U disclose a coating treatment method, which covers one or more layers of antibacterial coating on the surface of cellulose fibers. The antibacterial effect is excellent and the water washability is good, but the processing technology is relatively complicated. The antibacterial effect decreases significantly after the coating is worn, and its antibacterial effect is restricted by the wear of the coating. Patent CN106758254B discloses an immersion-baking antibacterial finishing method, in which Lyocell fabric is immersed in a prepared polyethyleneimine guanidine hydrochloride polymer solution to cause a cross-linking reaction, and finally baked, washed, and dried to obtain Lyocell fabric with antibacterial function, which has good antibacterial effect and excellent water washability; however, the preparation steps of this method are relatively cumbersome and the cost is high.
[0004] The antibacterial finishing by blending directly adds the antibacterial components to the spinning solution, and then directly spins the antibacterial fiber after blending. The method has a simple process flow, and the product has a long-lasting antibacterial effect. It is the most convenient process-based antibacterial finishing method. Patent CN104975366B discloses a Lyocell fiber doped with nanoparticles by a blending method, which imparts antibacterial properties to the fiber by adding nanosilver particles to the spinning solution. However, nanosilver is too expensive, which limits its application in antibacterial fibers. Copper and its complexes have a broad-spectrum bactericidal effect and are relatively cheap, but for the traditional Lyocell process, the introduction of copper will cause the system to degrade significantly, affecting the fiber quality, and may explode at high temperatures. Summary of the invention
[0005] In view of the defects of the prior art and the need for improvement, the present invention provides an antibacterial Lyocell fiber and a preparation method thereof, aiming to solve the technical problem that the application of the existing blended antibacterial finishing method is limited.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing an antibacterial Lyocell fiber, comprising the following steps:
[0007] S1. Mix NMMO powder, water, alcohol solution and antibacterial agent and obtain antibacterial agent dispersion by ultrasonic treatment; wherein the antibacterial component of the antibacterial agent is selected from one or more of nano copper, CuO and Cu2O; the ultrasonic temperature is 25-40°C, and the ultrasonic time does not exceed 2h;
[0008] S2, mixing NMMO powder and water and heating and stirring to obtain a NMMO solution;
[0009] S3, adding cellulose to the NMMO solution, and continuing to heat and stir until the cellulose is completely dissolved to obtain a cellulose solution;
[0010] S4, mixing the antibacterial agent dispersion with the cellulose solution, and stirring to obtain a spinning solution;
[0011] S5. Inject the spinning solution into a syringe, extrude it, pass through an air layer of 5-20 mm and enter a coagulation bath, and then wash and dry it to obtain antibacterial Lyocell fibers.
[0012] Preferably, in step S1, the initial mass fraction of the antibacterial agent does not exceed 3.4%.
[0013] Preferably, in step S1, the alcohol solution for dissolving NMMO comprises one or more of lower monohydric and polyhydric alcohols.
[0014] Preferably, in step S2, the heating temperature is 80-110°C, the stirring speed is 200-500 rpm, and the stirring time is 10-20 min.
[0015] Preferably, in step S3, the heating temperature is 80-110° C., the stirring speed is 800-1500 rpm, and the stirring time is 0.5-1.5 h; and the mass fraction of cellulose in the NMMO solution does not exceed 10%.
[0016] Preferably, in step S4, the stirring speed is 900-1500 rpm, the temperature is 30-50° C., and the stirring time is 1-3 h.
[0017] Preferably, in step S5, the spinning temperature ranges from 15 to 50°C.
[0018] Preferably, in step S5, the coagulation bath comprises a mixed solution of one or more of water, methanol and ethanol.
[0019] In a second aspect, the present invention provides an antibacterial Lyocell fiber, which is prepared by the preparation method described in the first aspect.
[0020] Preferably, the antibacterial component in the antibacterial Lyocell fiber accounts for 0.1-30% of the total weight of the fiber.
[0021] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects:
[0022] 1. The present invention first mixes the antibacterial component with the NMMO alcohol solution at room temperature, and then adds it to the cellulose solution. Since the alcohol solution is introduced into the system, the antibacterial agent dispersion still has good fluidity at room temperature, thereby overcoming the problem that the introduction of copper will cause the system to degrade significantly and affect the fiber quality, and may explode at high temperatures; at the same time, the doped particles are more evenly dispersed in the cellulose / NMMO / alcohol / water system, reducing the agglomeration of particles, thereby avoiding the blockage of the spinneret during the spinning process, which is conducive to the smooth progress of the spinning process.
[0023] 2. The present invention can reduce the degradation of copper to the spinning solution, and the prepared copper-based antibacterial Lyocell fiber can still maintain a good effect after multiple washings; at the same time, the antibacterial components are mainly inorganic particles, which are easy to remove and will not have a major impact on subsequent solvent recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a comparison chart of the rheological scans of the spinning solutions prepared in Comparative Example 1 and Example 4 of the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, system composition, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0026] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0027] Mechanical properties are important indicators for evaluating Lyocell fibers. The present invention uses a 5943 universal material testing machine from INSTRON Corporation of the United States to obtain the mechanical properties. Before the test, the Lyocell fibers are balanced for 12 hours at a temperature of 23°C and a humidity of 65%. During the test, the sample stretching speed is 20 mm / min and the test length is 20 mm, that is, under pre-tension, the length of the fiber sample is 20 mm.
[0028] In the following specific embodiments of the present invention, the antibacterial properties of Lyocell fibers are characterized by the following antibacterial properties testing method, and the specific antibacterial properties testing method is as follows:
[0029] The antibacterial quantitative test was carried out with reference to the national standard GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method. The experimental bacteria were Escherichia coli (ATCC 11229) and Staphylococcus aureus (ATCC 6538), and the control sample was 100% cotton fabric without any treatment.
[0030] 1) Inoculate the standard strains of Staphylococcus aureus and Escherichia coli on two agar plates respectively, and culture them for three generations. Pick the colonies and make a bacterial suspension in PBS buffer solution. Take a certain amount of bacterial suspension and culture it on the plate for 24 hours. Count the number of colonies and use it as the blank sample colony number to judge the effectiveness of the experiment.
[0031] 2) A certain amount of bacterial suspension is placed in a conical flask, and a certain amount of PBS buffer is added to dilute it. Finally, the antibacterial fiber prepared in the embodiment of the present invention is sterilized by high pressure and added into the conical flask so that it is completely in contact with the bacterial solution, and the bottle stopper is covered.
[0032] 3) Place the conical flask in step 2) on a constant temperature oscillator at 25°C and an oscillation rate of 250 r / min for 1 min, then take out a certain amount of bacterial solution, dilute it with PBS buffer to an appropriate multiple, and then culture it on an agar medium for 24 h as the "0" contact sample. Count the number of colonies to determine the effectiveness of the experiment.
[0033] 4) After the sample with "0" contact sampling completed in step 3) was placed on a constant temperature oscillator for 18 hours at 25°C and an oscillation rate of 150 r / min, a certain amount of bacterial suspension was diluted with PBS buffer by a certain multiple, and then placed on a culture medium for 24 hours to count the number of colonies for calculating the antibacterial rate. The antibacterial fiber prepared in each embodiment was measured three times and the average value was calculated.
[0034] 5) Calculate the experimental results according to the following formula:
[0035] Calculation of live bacteria concentration: K = Z × R
[0036] K: viable bacteria concentration (CFU / ml)
[0037] Z: Number of colonies on the plate
[0038] R: dilution factor
[0039] Experimental validity judgment: F = lgW t -lgW0
[0040] F: Growth value of sample experimental bacteria
[0041] W t :The average value of viable bacteria concentration in conical flasks after 18h oscillation contact of 3 control samples (CFU / ml)
[0042] W0: Average value of viable bacteria concentration in conical flasks at contact time "0" for three control samples (CFU / ml) Calculation of antibacterial rate:
[0043] Y: Experimental antibacterial rate
[0044] W t :The average value of viable bacteria concentration in conical flasks of 3 control samples after 18h shaking (CFU / ml)
[0045] Q t :The average value of viable bacteria concentration in conical flasks after 18h shaking of 3 antibacterial fibers (CFU / ml)
[0046] The present invention is further described below by means of specific embodiments.
[0047] Comparative Example 1
[0048] A method for preparing antibacterial Lyocell fiber comprises the following steps:
[0049] S1. Add 20.62 g of anhydrous NMMO and 2.45 g of deionized water into a three-necked flask, and heat and stir for 5 min to obtain a NMMO solution with a water content of 10 wt%, wherein the heating temperature is 100° C. and the stirring rate is 20 rpm.
[0050] S2. Add 1.21 g of cellulose wood pulp to the NMMO solution in step S1, maintain the temperature at 100°C, increase the stirring rate to 900 rpm, and continue stirring for 30 minutes to obtain a transparent cellulose solution. The cellulose wood pulp is obtained by the following method: crushing cellulose wood pulp with a degree of polymerization of 400-800 into fragments with a length of 0.1-0.5 mm, and drying in an oven at 60°C for 12 hours.
[0051] S3, adjusting the stirring rate to 1200 rpm, keeping the temperature unchanged, adding 0.0374 g of copper oxide powder to the cellulose solution prepared in step S2, stirring continuously for 60 min and then degassing to obtain the antibacterial Lyocell fiber spinning solution.
[0052] S4. Inject the spinning solution obtained in step S3 into a syringe, with an air gap of 10 mm between the needle and the coagulation bath (water), an injection flow rate of 0.2 ml / m, and spin cellulose filaments at 80° C. by a push pump, with a copper oxide solid content of 3%.
[0053] Example 1
[0054] A method for preparing antibacterial Lyocell fiber comprises the following steps:
[0055] S1. Weigh 10.31 g NMMO, 4.14 g ethanol, 1.22 g water and 0.0012 g copper oxide in a 50 ml sample bottle, mix them and dissolve them by ultrasonication to obtain an antibacterial agent dispersion, wherein the ultrasonic temperature is 30° C. and the ultrasonic time is 30 min.
[0056] S2. Add 10.31 g of anhydrous NMMO and 1.22 g of deionized water into a three-necked flask, and heat and stir for 5 min to obtain an NMMO solution with a water content of 10 wt%, wherein the heating temperature is 100° C. and the stirring rate is 20 rpm.
[0057] S3, adding 1.21g of cellulose wood pulp to the NMMO solution in step S2, maintaining the temperature at 100°C, increasing the stirring rate to 900rpm, and continuously stirring for 30min to obtain a transparent cellulose solution. The cellulose wood pulp is obtained by the following method: crushing cellulose wood pulp with a degree of polymerization of 400-800 into fragments with a length of 0.1-0.5mm, and drying in an oven at 60°C for 12h.
[0058] S4. After moving the three-necked flask to a 30°C air bath, add the antibacterial agent dispersion prepared in step S1 to the cellulose solution prepared in step S3, continue stirring for 60 minutes, and then degas to obtain the antibacterial Lyocell fiber spinning solution.
[0059] S5. Inject the spinning solution obtained in step S4 into a syringe, with an air gap of 10 mm between the needle and the coagulation bath (water), an injection flow rate of 0.2 ml / m, and spin cellulose filaments at 30° C. by a push pump, with a copper oxide solid content of 0.1%.
[0060] Embodiment 2-10
[0061] The method for preparing antibacterial Lyocell fiber provided in Example 2-10 is different from that in Example 1 in that the composition and content of the antibacterial agent in step S1 are changed. Except for the above differences, other operations are the same and will not be repeated here. The specific experimental conditions and measurement results are shown in Table 1.
[0062] Table 1
[0063]
[0064] Comparing Example 1 with Examples 2-7, it can be seen that as the copper oxide content increases, the strength of the Lyocell fiber first increases and then decreases, while its antibacterial rate shows an upward trend. This is because doping a small amount of inorganic particles in the spinning solution can improve the orientation and crystallinity of the fiber during the molding process, achieving a reinforcing effect; but as the doping ratio increases, the two incompatible phases will inevitably separate, and then the fiber strength decreases.
[0065] By comparing Example 1 with Example 8, it can be seen that when the contents of cupric oxide and cuprous oxide are the same, the strength of the Lyocell fiber does not change much, but cuprous oxide has a better antibacterial effect than cupric oxide. This is because for the same contents of cupric oxide and cuprous oxide, cuprous oxide has a higher copper content and thus has a better antibacterial effect.
[0066] Examples 11-17
[0067] The preparation method of antibacterial Lyocell fiber provided in Examples 11-17 is different from that in Example 4 in that the continuous stirring speed, stirring time and stirring temperature in step S4 are changed. Except for the above differences, other operations are the same and will not be repeated here. The specific experimental conditions and measurement results are shown in Table 2.
[0068] Table 2
[0069]
[0070] By comparing Examples 4, 11 and 12, it can be seen that when the antibacterial agent content is 3%, the stirring speed has almost no effect on the fiber strength. This is because the dispersion of copper oxide in the system directly affects the final strength of the fiber. Under the conditions of a stirring speed of 900 rpm and a stirring time of 1 h, the copper oxide particles are already evenly distributed in the system, and further increasing the stirring speed will not have much effect on the dispersion of the particles.
[0071] It can be seen from the comparison of Examples 12-15 that, at 30°C, the stirring time has little effect on the fiber strength. On the one hand, this is because the copper oxide is already distributed uniformly enough in the system, and extending the time has no significant effect on the distribution of the doped particles. On the other hand, at 30°C, the catalytic degradation effect of copper oxide on the system is greatly slowed down.
[0072] By comparing Examples 13, 16 and 17, it can be seen that the mechanical properties of the fiber decrease significantly with the increase of the stirring temperature. This is because the increase in stirring temperature promotes the catalytic degradation of NMMO by copper, which ultimately affects the quality of the fiber.
[0073] Examples 18-23
[0074] The preparation method of antibacterial Lyocell fiber provided in Examples 18-23 is different from that in Example 4 in that the spinning temperature in step S5, the air gap between the needle and the coagulation bath (water), and the pump infusion flow rate are changed. Except for the above differences, other operations are the same and will not be repeated here. The specific experimental conditions and measurement results are shown in Table 3.
[0075] Table 3
[0076]
[0077] By comparing Examples 4, 18 and 19, it can be seen that increasing the spinning temperature helps to improve the fiber strength. This is because the viscosity of the spinning solution is lower at a higher temperature, and it is easier to orient during the spinning process, thereby having higher mechanical strength.
[0078] By comparing Examples 4, 20 and 21, it can be seen that increasing the spinning air gap helps to improve the fiber strength. A larger spinning air gap allows the spinning solution to have more opportunities to be oriented before solidification, thereby obtaining better-oriented fibers.
[0079] By comparing Examples 4, 22 and 23, it can be seen that an excessively large perfusion flow rate will reduce the strength of the fiber. The greater the perfusion flow rate, the shorter the time the fiber stays in the air segment for stretching, the fiber orientation is affected, and the strength decreases.
[0080] Experiment 1
[0081] The Lyocell fibers prepared in Examples 1-7 were subjected to a water wash resistance and antibacterial performance test. The experimental results are shown in Table 4.
[0082] Table 4
[0083]
[0084]
[0085] From the results of the antibacterial performance experiment (Table 4), it can be seen that the copper-based antibacterial Lyocell fiber prepared using the stock solution blending method of the present invention has excellent antibacterial properties and a high antibacterial rate. After 50 washes, the antibacterial rate of the copper oxide Lyocell fiber with a solid content of 15% remains at 100%; controlling the amount of antibacterial components added can change the water washability of the fiber.
[0086] Test 1
[0087] In order to more intuitively evaluate the superiority of the present invention in controlling the degradation of the spinning solution, the spinning solutions of Comparative Example 1 and Example 4 were subjected to rheological scanning using a TA rheometer (the test temperature was 80° C.). Figure 1 .
[0088] Test 1 shows that the preparation method of the present invention can effectively reduce the degradation of the system by copper, and while imparting antibacterial function to the fiber, it retains the spinnability of the spinning solution and the fiber quality to the maximum extent.
[0089] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing antibacterial Lyocell fiber, characterized in that: The steps include: S1. Mix NMMO powder, water, alcohol solution and antibacterial agent and obtain antibacterial agent dispersion by ultrasonic treatment; wherein the antibacterial component of the antibacterial agent is selected from one or more of nano copper, CuO and Cu2O; the ultrasonic temperature is 25-40°C, and the ultrasonic time is not more than 2h; S2, mixing NMMO powder and water and heating and stirring to obtain a NMMO solution; S3, adding cellulose to the NMMO solution, and continuing to heat and stir until the cellulose is completely dissolved to obtain a cellulose solution; S4, mixing the antibacterial agent dispersion with the cellulose solution, and stirring to obtain a spinning solution; S5. Inject the spinning solution into a syringe, extrude it, pass through an air layer of 5-20 mm and enter a coagulation bath, and then wash and dry it to obtain antibacterial Lyocell fibers.
2. The method for preparing an antibacterial Lyocell fiber according to claim 1, characterized in that: In step S1, the initial mass fraction of the antibacterial agent does not exceed 3.4%.
3. The method for preparing an antibacterial Lyocell fiber according to claim 1, characterized in that: In step S1, the alcohol solution for dissolving NMMO includes one or more of lower monohydric and polyhydric alcohols.
4. The method for preparing an antibacterial Lyocell fiber according to claim 1, characterized in that: In step S2, the heating temperature is 80-110°C, the stirring speed is 200-500 rpm, and the stirring time is 10-20 min.
5. The method for preparing an antibacterial Lyocell fiber according to claim 1, characterized in that: In step S3, the heating temperature is 80-110° C., the stirring speed is 800-1500 rpm, and the stirring time is 0.5-1.5 h; and the mass fraction of cellulose in the NMMO solution does not exceed 10%.
6. The method for preparing an antibacterial Lyocell fiber according to claim 1, characterized in that: In step S4, the stirring speed is 900-1500 rpm, the temperature is 30-50° C., and the stirring time is 1-3 h.
7. The method for preparing antibacterial Lyocell fiber according to claim 1, characterized in that: In step S5, the spinning temperature ranges from 15 to 50°C.
8. The method for preparing antibacterial Lyocell fiber according to claim 1, characterized in that: In step S5, the coagulation bath includes one or more mixed solutions of water, methanol, and ethanol.
9. An antibacterial Lyocell fiber, characterized in that: The antibacterial Lyocell fiber is prepared by the preparation method according to any one of claims 1 to 8.
10. The antibacterial Lyocell fiber according to claim 9, characterized in that: The antibacterial component in the antibacterial Lyocell fiber accounts for 0.1-30% of the total weight of the fiber.
Citation Information
Patent Citations
A kind of lyocell fiber containing nanoparticles and preparation method thereof
CN104975366B
An antibacterial Lyocell fabric and its preparation method
CN106758254B
Antibacterial cellulose fiber
CN210916769U
Antibacterial cellulose fiber
CN214193550U